2015
DOI: 10.1007/s11306-015-0793-8
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting individual breast cancer risk using plasma metabolomics and biocontours

Abstract: Breast cancer is a major cause of death for women. To improve treatment, current oncology research focuses on discovering and validating new biomarkers for early detection of cancer; so far with limited success. Metabolic profiling of plasma samples and auxiliary lifestyle information was combined by chemometric data fusion. It was possible to create a biocontour, which we define as a complex pattern of relevant biological and phenotypic information. While single markers or known risk factors have close to no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…An interesting epidemiological study demonstrated accurate prediction of breast cancer several years ahead of its clinical detection based on the combined analysis of serum NMR metabolic profiles and lifestyle variables, referred to as biocontours. 105 While mammography can diagnose current breast cancer with a sensitivity and specificity of ~75%, respectively, the new approach can predict the breast cancer risk 2–5 years ahead with sensitivity and specificity above 80%. This study was made using the samples from women enrolled in the Danish Diet, Cancer and Health cohort enrolled in the years 1993–1997.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting epidemiological study demonstrated accurate prediction of breast cancer several years ahead of its clinical detection based on the combined analysis of serum NMR metabolic profiles and lifestyle variables, referred to as biocontours. 105 While mammography can diagnose current breast cancer with a sensitivity and specificity of ~75%, respectively, the new approach can predict the breast cancer risk 2–5 years ahead with sensitivity and specificity above 80%. This study was made using the samples from women enrolled in the Danish Diet, Cancer and Health cohort enrolled in the years 1993–1997.…”
Section: Applicationsmentioning
confidence: 99%
“…Red curve: validation using independent data obtained in 1997. Reproduced from Bro, R.; Kamstrup-Nielsen, M. H.; Engelsen, S. B.; Savorani, F.; Rasmussen, M. A.; Hansen, L.; Olsen, A.; Tjønneland, A.; Dragsted, L. O. Metabolomics 2015, 11, 1376–1380 (ref 105). …”
Section: Figurementioning
confidence: 99%
“…54 Most recently, metabolic profiling of plasma samples and auxiliary lifestyle information has led to the development of so-called biocontours, which may forecast higher risk of breast cancer two-to-five years after the sample is taken, opening the possibility of timely prediction of individual cancer risk and thus more efficient screening. 55 On the other hand, clinical or pathologic markers that can reliably identify the subset of patients with DCIS at greatest risk of developing invasive breast cancers -a crucial population in the overdiagnosis and overtreatment debate -have yet to be identified. 56 As medical professionals, we must find better ways to communicate the benefits and risks of screening to patients.…”
Section: Not Less Detection But More Informationmentioning
confidence: 99%
“…Similar unique metabolic patterns have been identified in lung cancer [124] and oral squamous cell carcinoma pathways [125] as well. By incorporating a more integrative approach, Bro and colleagues recent created Biocontour [126], a novel risk assessment scale that combines metabolic profile analysis of plasma samples and relevant lifestyle information to predict cancer risk. With a sensitivity and specificity superior to traditional screening mammography, Biocontour was shown to predict individual diagnoses of breast cancer several years ahead of diagnosis [126].…”
Section: Addressing Challenges For Future Clinical Trialsmentioning
confidence: 99%